Intestinal parasitic infection with special reference to taeniid tapeworms in school children of Malakand region, Pakistan - Rahman H. U.; Rafiq N.; Khan W.; De Los Ríos Escalante P.; Aldamigh M. A. (Helminthologia)
Diseases caused by intestinal parasites impose a substantial burden on the population of middle-income countries, including Pakistan. This research aimed to assess the risk factors for intestinal parasites in Malakand, Pakistan, school children. Three hundred sixty stool samples were collected from school children, of which 140 (39 %) tested positive for helminth, including taenids. The wet mount preparation in saline/iodine/methods was used for stool examination. The GraphPad Prism of version 5 was used to analyze the data, and the P value was considered significant when it was less than 0.05 % (at 95 % CI). Males were more infected at 40.7 % compared to female students at 33.3 %. (P>0.005 at 95 % CI). Among the helminth Ascaris lumbricoides was the most prevalent 30.71 % (n=43), taeniid species 22.85 % (n=32), Hookworms12.14 % (n=17), Hymenolepis nana 10 % (n=14), Enterobius vermicularis 7.85 % (n=1), Hymenolupis diminuta 6.42 % (n=9), and Trichuris trichiura 5.71 % (n=8) were reported. Age-wise prevalence was noted as the students aged 11 to 13 years were highly infected at 57.4 %, followed by 8 to 10 years at 48.8 %, while the least prevalence was noted in the age 5 to 7 years at 45.5 %. (P>0.005 at 95 % CI). Regarding the association of intestinal parasitic infection and nutritional status of the students, 53.0 % had 10 to 11 inches in diameter upper arm circumference, and 49.4 % had 8 to 9 inches in upper arm circumference (P>0.05). Information on the students’ locality and intestinal parasitic infection shows that students in rural areas were more infected, 54.1 %, compared to urban areas, 41.1 % (P value is 0.023 at 95 % CI). Based on the pattern of infection, 19.44 % (n=70/360) were single, 10.5 % (n=38/360) double, 6.11 % (n=22/360), and 2.77 % (n=10/360) quadruple infections had been recorded. The symptoms were abdominal pain, constipation, nausea or vomiting, stomach pain, blotting, and Diarrhea appearing after the taeniid infection. We conclude that since deworming is insufficient to control parasitic illnesses, there is a need for widespread campaigns to raise awareness about children’s health and hygiene, as well as the necessity for the creation of efficient poverty control programs.